2020
DOI: 10.1038/s41430-019-0552-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oropharyngeal administration of colostrum on the incidence of necrotizing enterocolitis, late-onset sepsis, and death in preterm infants: a meta-analysis of RCTs

Abstract: Necrotizing enterocolitis (NEC) and late-onset sepsis (LOS) are two major contributors to death among preterm infants. Oropharyngeal administration of colostrum (OAC) has been proved as an easy, safe, and economically viable technique to help preterm neonates to build up their immunity. In this review, we assessed the effects of OAC on preterm infants. Several mainstream databases were searched including PubMed, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), and a website of clinical trials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 50 publications
4
38
0
7
Order By: Relevance
“…Biological studies have shown that OAC affects the prevention of NEC through the following mechanisms: (a) The cytokines in breastmilk interact with the oropharyngeal lymphoid tissue system, which causes T cell activation and leads to immune activation and anti-in ammatory reactions of can directly protect the immune cells in the oropharynx and can reach the intestinal tract to protect the mucosal barrier from oxidative damage, preventing oxidative stress-induced intestinal ora changes and translocation [24][25][26][27] . Although biological theory supports the results of these studies, most clinical studies and meta-analyses published in recent years have indicated that OAC cannot reduce the incidence of NEC [28][29][30][31] .…”
Section: Oac In Preventing Necmentioning
confidence: 92%
See 1 more Smart Citation
“…Biological studies have shown that OAC affects the prevention of NEC through the following mechanisms: (a) The cytokines in breastmilk interact with the oropharyngeal lymphoid tissue system, which causes T cell activation and leads to immune activation and anti-in ammatory reactions of can directly protect the immune cells in the oropharynx and can reach the intestinal tract to protect the mucosal barrier from oxidative damage, preventing oxidative stress-induced intestinal ora changes and translocation [24][25][26][27] . Although biological theory supports the results of these studies, most clinical studies and meta-analyses published in recent years have indicated that OAC cannot reduce the incidence of NEC [28][29][30][31] .…”
Section: Oac In Preventing Necmentioning
confidence: 92%
“…Many studies have shown that OAC may also have the advantages of lowering the age of achieving full enteral feeding and full oral feeding, reducing the incidence of feeding intolerance [29,30,34,36] , increasing the body weight at the correct gestational age of 36 weeks [38] , reducing the length of hospital stay [29,31,39] , and prolonging the days of breastfeeding [40] . In our study, it was also observed that the age of achieving full enteral feeding was lower in the OAC group, which is of great signi cance for the management of premature infants.…”
Section: The Role Of Oac In Preventing Other Complicationsmentioning
confidence: 99%
“…However, the American Academy of Pediatrics advises that breastmilk has superior nutrition, especially for preterm infants, who should all receive human milk [1]. The oropharyngeal administration of the mother's colostrum in preterm infants has recently become a subject of numerous randomized controlled trials to assess the intervention in terms of reducing the incidence of late-onset sepsis and necrotizing enterocolitis, and it is recommended for the routine care of preterm infants in the neonatal intensive care unit [2]. The effect is attributed to a high content of protective immune and trophic biofactors in breastmilk, such as cytokines, lactoferrin, oligosaccharides and antioxidants [3].…”
Section: Introductionmentioning
confidence: 99%
“…23 Meta-analysis of RCTs has shown that oropharyngeal administration of colostrum in preterm infants has positive effect on the incidence of NEC, late-onset sepsis, and mortality. 24 However, the benefit of early feeding in ultra-LBW requires further studies.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings of short term outcome in terms of in-hospital mortality of 14 (13.20%) out of 106 NEC is comparable and somewhat better than published reports. 24,29,30 The year by year increase in the incidence of NEC from 2.90 in 2014 to 12.99/1000 in 2018 may be the reflection of improvement in overall maternal and child health care, with better survival of preterm and LBW babies, and increase in NEC. The babies who survive the assault of NEC have the possibility of poor physiological and neurodevelopmental growth, due to intestinal failure, strictures, short bowel syndrome, frequent hospitalization.…”
Section: Methodsmentioning
confidence: 99%